Planetary Roller Hub-type Continuously Variable Transmission - Wang Shaoteng; Song Aiping; Huang Jiaming; Jiang Kaijia (Jixie chuandong)
The wheel motor drive has the problem of insufficient power at low speeds when climbing hills. In this study, a new planetary roller wheel continuously variable transmission (CVT) is developed, which achieves independent variable speed drive of the wheel hub by means of multiple sets of roller friction drives. The inner ring of the wheel is an internal gear ring, driven by multiple planetary distribution gears to increase the wheel drive power. The actual working radius of the centre and distribution wheels is changed by controlling the angle of oscillation of the friction rollers to achieve continuity and stability of the speed change process. Motion simulation experiments using Adams software conclude that the CVT has a smooth and continuous speed, high transmission efficiency and smooth motion.